2006
DOI: 10.1124/jpet.106.105445
|View full text |Cite
|
Sign up to set email alerts
|

Periplocoside E Inhibits Experimental Allergic Encephalomyelitis by Suppressing Interleukin 12-Dependent CCR5 Expression and Interferon-γ-Dependent CXCR3 Expression in T Lymphocytes

Abstract: Periplocoside E (PSE) was found to inhibit primary T-cell activation in our previous study. Now we examined the effect and mechanisms of PSE on the central nervous system (CNS) demyelination in experimental allergic encephalomyelitis (EAE). C57BL/6 mice immunized with myelin oligodendrocyte glycoprotein (MOG) were treated with PSE following immunization and continued throughout the study. The effect on the progression of EAE and other relevant parameters were assessed. PSE reduced the incidence and severity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…We have previously shown that Periplocoside E (PSE), a compound isolated from P. sepium Bge, inhibits primary T cell activation by blocking the ERK and JNK pathway and delaying IL-2Rα (CD25) expression [21]. We also found that Periplocoside E inhibits Experimental Allergic Encephalomyelitis by suppressing IL-12-dependent CCR5 expression and IFN-γ-dependent CXCR3 expression in T lymphocytes [22]. Here, Periplocoside A (PSA), a pregnane glycoside, is a new compound isolated from P. sepium Bge.…”
Section: Introductionmentioning
confidence: 92%
“…We have previously shown that Periplocoside E (PSE), a compound isolated from P. sepium Bge, inhibits primary T cell activation by blocking the ERK and JNK pathway and delaying IL-2Rα (CD25) expression [21]. We also found that Periplocoside E inhibits Experimental Allergic Encephalomyelitis by suppressing IL-12-dependent CCR5 expression and IFN-γ-dependent CXCR3 expression in T lymphocytes [22]. Here, Periplocoside A (PSA), a pregnane glycoside, is a new compound isolated from P. sepium Bge.…”
Section: Introductionmentioning
confidence: 92%
“…We did not observe any statistically significant differences between VBP15 and prednisolone treatment with regard to disease severity, incidence, and histopathology. Furthermore, expression profiling of transcripts in spinal cord tissue revealed that VBP15 treatment led to significant reductions of several proinflammatory mediators including Ccl19, Ccl6, Ccl5, Ccl3, Ccl9, Cxcr4, Ccr2, Ccr5, Il-7, Il-16, Il-1a, Tgfb1, Irf1, Tnfsf13b, Tnfrsf13b, Tnfrsf4, Tnfsf12, Il-7r, Tlr2, Tlr9, Tlr8, Cd40, Icam1, and Vcam1 (Table 1), all of which have been previously shown to be associated with EAE pathogenesis (Alt et al 2002;Arima et al 2012;Baron et al 1993;Becher et al 2001;Bullard et al 2007;Desplat-Jego et al 2002;Fife et al 2000;Karpus and Kennedy 1997;Kohler et al 2008;Lee et al 2011;Li et al 2013;Matsuki et al 2006;Nohara et al 2001;Prinz et al 2006;Reboldi et al 2009;Ren et al 2011;Reynolds et al 2010;Skundric et al 2005;Szczucinski and Losy 2011;Veldhoen et al 2006;Zhou et al 2011;Zhu et al 2006). …”
Section: Vbp15 Reduces Cns Inflammation In Murine Experimental Autoimmentioning
confidence: 99%
“…The involvement of Th17 cells in the pathogenesis of EAE not only challenged the Th1-Th2 paradigm, but also provided insights to help elucidate the mechanisms of action for these new compounds. Our previous work demonstrated that PSE inhibited EAE through suppressing Th1-subtype cytokine-dependent chemokine receptor expression [12] . Indeed, we also observed a reduced production of IL-2 and IFN-γ in PSA-treated group in the present work ( Figure 3C, 3D).…”
Section: Discussionmentioning
confidence: 99%
“…Two pregnane glycosides, PSA and PSE, have been previously studied for their immunosuppressive effects in vivo and in vitro [11][12][13] . However, due to the low solubility of these large organic compounds, all previous studies were based on the intraperitoneal route of administration, which might impede the development of these compounds as perspective drug candidates for human autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation